Assessment of decreased ovarian reserve and systemic inflammatory markers: Ovarian reserve and inflammatory markers - Shoarishoar, Seyedeh shahed; KaboodMehri, Roya; Fakor, Fereshteh; Rafiei Sorouri, Zahra; Mansour-Ghanaei, Mandana; Faraji Darkhaneh, Roya; Dalil Heirati, Seyedeh Fatemeh; Karimian, Maryam; Heidarpour, Zahra; Milani, Forozan; Jalali, Fereshtehsadat (Cellular and Molecular Biology, 2024)
Given the significance of investigating ovarian reserve in infertile women, the limitations of existing diagnostic tests, and the absence of similar studies in this area, the present study aimed to examine the relationship between systemic inflammatory markers in patients with diminished ovarian reserve referred to the fertility clinic of Alzahra Hospital in Rasht in the year 2023. This cross-sectional analytical study was conducted on 174 patients referred to the Alzahra Hospital fertility clinic in Rasht. Patients were divided into two categories based on their serum levels of anti-Müllerian hormone (AMH):AMH >1.1 (ng/ml) and AMH < 1.1(ng/ml). Demographic and laboratory variables, including age, BMI, parity, neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), red cell distribution width-to-platelet ratio (RPR), and follicle-stimulating hormone (FSH), were compared between the two groups. Significant difference between the two study groups regarding age and BMI, with the mean age and BMI of patients in the group with normal ovarian reserve being lower than those in the group with poor ovarian reserve. There was a significant difference in FSH levels, the group with poor ovarian response had higher FSH levels. Age and FSH were identified as independent predictive variables associated with diminished ovarian reserve in patients. According to the present study, a significant association between diminished ovarian reserve and inflammatory markers (NLR, PLR, and RPR) was not observed. However, FSH levels were significantly higher in the Diminished Ovarian Reserve (DOR) group. Furthermore, a meaningful correlation was only found between diminished ovarian reserve and age.